2012
DOI: 10.1093/intimm/dxs056
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 contributes to cardiac fibrosis following experimental autoimmune myocarditis by a PKCβ/Erk1/2/NF-κB-dependent signaling pathway

Abstract: Myocarditis is a common clinical cardiovascular disease, and some patients progress to dilated cardiomyopathy (DCM) with chronic heart failure. Common viral infections are the most frequent cause of myocarditis, but other pathogens and autoimmune diseases have also been implicated. T(h)17 cells are novel IL-17-producing effector T helper cells that play an important role in the development of autoimmune myocarditis. Furthermore, IL-17 is also important in post-myocarditis cardiac remodeling and progression to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 34 publications
4
65
0
Order By: Relevance
“…IL-17 has been demonstrated to activate fibroblast proliferation via an Akt/miR-101/MKP-1-dependent p38 MAPK and ERK1/2 pathway [22] and fibrosis through the PKC β /Erk1/2/NF- κ B signaling pathway [23]. It was shown that the fibroblasts constitutively express the IL-17 receptor and IL-17A stimulates fibroblast proliferation and migration [22].…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 has been demonstrated to activate fibroblast proliferation via an Akt/miR-101/MKP-1-dependent p38 MAPK and ERK1/2 pathway [22] and fibrosis through the PKC β /Erk1/2/NF- κ B signaling pathway [23]. It was shown that the fibroblasts constitutively express the IL-17 receptor and IL-17A stimulates fibroblast proliferation and migration [22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment of BALB/c mice with anti-IL17A monoclonal antibody administered after the onset of EAM abrogated myocarditis-induced cardiac fibrosis and preserved ventricular function [5]. These observations, together with the evidence that IL-17A is able to directly signal the function of the cardiac fibroblast [25][26][27], indicate that this cytokine critically contributes to myocardial fibrosis and remodelling of the extracellular matrix, thus driving the progression to DCM.…”
mentioning
confidence: 82%
“…In addition to the hypertrophic and fibrotic responses by the classical pro-inflammatory cytokines, IL-17 also induces cardiac inflammation, hypertrophy, and fibrosis (46,47). TRAF3IP2 is a critical intermediate in IL-17 signaling (11,12).…”
Section: Trafip2 In Adverse Cardiac Remodelingmentioning
confidence: 99%
“…It induces cardiac fibroblast proliferation and migration via p38 MAPK and ERK1/2 activation and MKP-1 (mitogen-activated protein kinase phosphatase-1) inactivation (48). On the other hand, its gene deletion inhibits the onset of myocarditis and progression to inflammatory dilated cardiomyopathy (47). Furthermore, macrophage/ monocyte-derived IL-17A may induce TNF-␣, IL-1␤, MCP-1, and MMPs, which play a role in adverse cardiac remodeling (49).…”
Section: Trafip2 In Adverse Cardiac Remodelingmentioning
confidence: 99%